Height-dependent Slow Magnetoacoustic Wave Amplitude and Energy Flux in Sunspot Atmospheres - Y. Sanjay; S. Krishna Prasad; P. S. Rawat (The Astrophysical Journal)
Slow magnetoacoustic waves (SMAWs) have been considered a possible candidate for chromospheric heating in the past. This study analyzed 20 active regions observed between 2012 and 2016 to examine the amplitude and energy flux variation of SMAWs in the umbral atmosphere. Six different wavelength channels from the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory, covering regions from the photosphere to the low corona, were utilized for this purpose. The wave amplitude estimations show a gradual increase in 3 minute oscillation amplitude, peaking between 700 and 900 km, followed by a steady decrease; further, at altitudes greater than 1800 km, it appears to increase and decrease again. The corresponding energy flux, on the other hand, displays a steady and monotonous decrease with a significant reduction in value from approximately 3.32 ± 0.50 kW m ^−2 near the photosphere to about 6.47 ± 3.16 ×10 ^−4 W m ^−2 at an altitude of 2585 km. This decay may be attributed to radiative damping and shock dissipation in the lower altitudes and thermal conduction and viscosity in the higher altitudes. The missing flux is a factor of 3–15 lower than that required to counterbalance the chromospheric radiative losses.